Exploring the drivers of public sector financial performance: accountability, transparency, and governance perspectives - Reza Rahmadi Hasibuan; Bambang Widarno (Business, Accounting, and Knowledge Journal, 2026)
This study aims to analyze the effect of accountability, transparency, and governance on public sector financial performance. The background of this research is the increasing need for better financial management and institutional performance in public sector organizations. This study uses a quantitative approach with secondary data obtained from government financial reports and institutional disclosures. The data are analyzed using multiple regression analysis to test the effect of accountability, transparency, and governance on financial performance. The results show that accountability has a positive and significant effect on financial performance. Transparency also has a positive effect, indicating that openness in financial reporting can support better organizational performance. Governance is also found to have a significant influence on financial performance through the implementation of control systems and regulatory compliance. These findings indicate that accountability, transparency, and governance play an important role in improving public sector financial performance. This study is expected to provide empirical evidence for public sector accounting research and practical implications for policymakers in improving financial management systems.